Proceedings of the 14th Conference of the European Chapter of the Association for Computational Linguistics, Volume 2: Short Pa 2014
DOI: 10.3115/v1/e14-4002
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Strategies for Building Temporal Ontologies

Abstract: In this paper, we propose to build temporal ontologies from WordNet. The underlying idea is that each synset is augmented with its temporal connotation. For that purpose, temporal classifiers are iteratively learned from an initial set of time-sensitive synsets and different propagation strategies to give rise to different TempoWordNets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Uma expressão de tempo dada por "dois dias atrás" deve ser normalizada para "2020-03-12", caso o dia corrente seja "2020-03-14", por exemplo. Outras expressões, como "antes", "depois" e "durante", também são válidas (HASANUZZAMAN et al, 2014).…”
Section: Ontologias Temporaisunclassified
“…Uma expressão de tempo dada por "dois dias atrás" deve ser normalizada para "2020-03-12", caso o dia corrente seja "2020-03-14", por exemplo. Outras expressões, como "antes", "depois" e "durante", também são válidas (HASANUZZAMAN et al, 2014).…”
Section: Ontologias Temporaisunclassified
“…In the project, which was conducted by Hasanuzzaman et al (2014), a method for constructing a Tempo-wordnet was suggested. According to this method, the WordNet was augmented with temporal information by following a two-step process: in the first step, synsets of the WordNet are classified as atemporal or temporal.…”
Section: Related Workmentioning
confidence: 99%